Analisis Penerapan Akuntansi Ijarah Pada Hunian Berbasis Syariah di Kota Makassar - Aco Rachmad. M (JEKAMI Journal of Accounting, 2022)
This study aims to determine whether the Islamic pearl griya as a sharia entity in the city of Makassar, whose form of business is lodging and this is included in the form of Ijarah, namely Musta'jir and Mu'jir and there are Ujrah and shigat that have implemented a syariah-based recording system, namely PSAK. Sharia 101 and Ijarah Accounting PSAK 107. This study uses a qualitative method where data collection is carried out through the method of interviewing informants who are directly related to the object under study, in this case the owner and manager of the business. This research results in the conclusion that the recording system has not been implemented in accordance with the standards applicable to the sharia pearl business and there are various factors, namely 1. There are no employees who understand recording according to the Sharia PSAK, 2. Opinion that financial records are carried out until at this point that's enough